The Correlation Between Studnets’ Habit In Listening To English Pop Song And Their Speaking Skill - Dhanyssa, Filza Putri; Ikhsan, Khairi; Yelliza, Yelliza (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to determine the correlation between students' habits in listening to English pop songs and speaking ability. Researchers use the correlational method using the correlational method using a quantitative approach. There are two variables in this research. Students' habit of listening to English pop songs as the independent variable (variable X) and students' speaking ability as the dependent variable (variable Y). The students' habits in listening to English pop songs were obtained from the questionnaire, while the students' speaking ability was obtained from the speaking performance test results. The population of this study involved students of SMAN 1 Bukit Sundi in the 2023/2024 academic year consisting of 160 students. Samples were taken using a random sampling technique that is 20% as many as 32 students. From the results of calculating the correlation with SPSS 26, it can be seen that the correlation value is 0.051 which is interpreted as a positive correlation at a weak level. The result of the correlation between students' habit of listening to English pop songs is significantly correlated with speaking skill of (0.361) and of 0.349. Therefore, the correlation between students' habit of listening to English pop song of (0.361) is related to speaking skill and (0.349). The results of the correlation between students' habit in listening to English pop song with a significant correlation value with speaking skill (0.361) and (0.349). Therefore, the correlation between students' habit of listening to English pop song (0.361) correlated with the speaking skill (0,539).